DISPUTES SETTLEMENT OF BALI TRADITIONAL INHERITANCE THROUGH PEACE AGREEMENT - Anak Agung Istri Agung; I Nyoman Sukandia (NOTARIIL Jurnal Kenotariatan, 2021)
The inheritance and the division of inheritance that is felt to be unfair is often a source of dispute. The disputes that occur can sometimes be resolved by making a peace agreement between the disputing parties. The peace desired by the parties is, of course, expected to end disputes/conflict and to provide legal certainty among those in dispute. However, sometimes peace agreements that have been made between those in dispute are disputed again in court. This study aims to examine the settlement of Balinese traditional inheritance disputes through a binding peace agreement between the parties make it. The method used in this study is a normative legal research, using a statute approach and a case approach. The result of this study showed that the settlement of Balinese indigenous inheritance disputes through a binding peace agreement of the parties that make it if the peace agreement is made based on the validity of the agreement as stipulated in article 1320 of the Civil Code, based on good faith as the principles in the law of the agreement, and must be made in the form of a notary deed is in accordance with the provisions for conciliation in book III of the Civil Code.